Synthesis Features of Iron Oxide Nanopowders with High Magnetic and Sorption Properties - Lavrynenko, Sergiy; Mamalis, Athanasios G.; Sofronov, Dmitry; Odnovolova, Alexandra; Starikov, Vadym (Trans Tech Publications, 2018)
The magnetic particles of iron oxides are promising materials for the purification of water from ions of heavy metals and radionuclides. Their advantage compared to other sorbents is the ability to extract by applied magnetic field, which greatly simplifies the task of extraction, separation and processing in cleaning technologies. The aim of this work is investigation of temperature and concentration of iron in the solution effect on the phase composition, nanoparticle size and their magnetization. Phase magnetite in the sample increases with increasing temperature and the magnetization decreases slightly with increasing the initial concentration of iron in solution. We found that regardless of the conditions of deposition formed spherical particles whose average size ranges from 7 to 15 nm. The sorptive capacity of the particles is virtually independent of the phase composition and for cobalt is about 18 mg/g. For sorption-based material magnetic particles Fe3O4 recommended to carry out the deposition process at a temperature not lower than 80°C. The concentration of iron in solution must be within 0,15–0,3M. The particles obtained contain in their composition at least 90 wt.% of magnetite phase and are characterized by a magnetization in the range of 65–70 A·m2/kg. Also in the paper is comparing efficiency of extraction and sorptioncapacity for cobalt particles by different phase of magnetite and hematite.
Keywords: iron oxide nanoparticles; magnetization; sorption; synthesis